RF 마그네트론 스퍼터링 방법으로 증착된 CuS 박막의 구조적 및 광학적 특성에 대한 스퍼터링 전력의 영향 - 이상운(Sangwoon Lee); 신동혁(Donghyeok Shin); 손영국(Young Guk Son); 손창식(Chang Sik Son); 황동현(Donghyun Hwang) (Current Photovoltaic Research, 2020)
CuS thin films were deposited on glass substrates at room temperature by RF magnetron sputtering. The structural and optical properties of CuS thin films grown by varying RF-power from 40 W to 100 W were studied. From the XRD analysis, we confirmed hexagonal crystal structures grown in the preferred orientation of the (110) plane in all CuS thin films, and the intensity of the main diffraction peak increased in proportion to the increase of RF-power. In the case of CuS thin film deposited at 40W, small-sized particles formed a thin and dense surface morphology with narrow pore spacing, relatively. As the power increased, the grain size and grain boundary spacing increased sequentially. The peaks for the binding energy of Cu 2p3/2 and Cu 2p1/2 were determined at 932.1 eV and 952.0 eV, respectively. The difference in binding energy for the Cu2+ states was the same at 19.9 eV regardless of process parameters. The transmittance and band gap energy in the visible region tended to decrease with increasing sputtering powers.